Kepemimpinan Kepala Sekolah Berbaisi Kecerdasan Emosional di SMAN 1 Soppeng Riaja Kabupaten Barru Propinsi Sulawesi Selatan - UDDIN, SARIF (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2016)
This study is aimed at investigating; (1) What is the purpose of principal leadership emotional intelligence based at SMA 1 Soppeng Riaja, Barru Regency? (2) How does the effort of the application of principal leadership emotional intelligence based conducted by the principal of State School of Senior High School 1 Soppeng Riaja Barru? To answer these problems researcher used qualitative approach. The methods of data collection are: (a) observation, (b) interview, and (c) documentation. While the methods of data analysis used analytical descriptive and reported with thick description. The results of the data analysis illustrated that; (1) The purposes of principal leadership emotional intelligence based at SMAN 1 Soppeng Riaja, Barru are: to improve the content standard and school competence, to improve standards of learning process, to improve the standard of learning process, to improve the standard of facilities and infrastructure, to improve school management standards, to improve financial standards, to improve the standard of educational assessment, and to improve the school readiness and external support. (2) The implementation of leadership through four aspects of emotional intelligence. The first, the current situation is the control emotion that caused by the events of life, work pressure, and the pressure of personal problems in doing tasks and responsibilities. The second, understanding of emotional intelligence is understanding the feelings of self and others in controlling the expression of emotions and get benefit of the potential of emotions as a source of energy and resources. The third, the ability of emotional intelligence is self-actualizing potential that include intentionality, creativity, toughness, and interpersonal relationship to motivate and mobilize their staff to work together to participate in the success of school organizational goals. The fourth, values and beliefs of emotional intelligence is prioritization of affection, angle of view, intuition, personal power and integrity in carrying out the policies and in collaboration with his staff.